Analisis Pendapatan Usaha Rumah Potong Ayam (Rpa) Di Kabupaten Rembang - Wahyu Dwi Suci Damayanti; Siswanto Imam Santoso; Titik Ekowati (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2021)
Analyze the income of a chicken slaughterhouse (RPA) in Rembang Regency. Chicken meat contains animal protein ranging from 16% to 22%, so it continues to be developed to meet the nutritional needs of the community. This study aims to analyze the income of a chicken slaughterhouse (RPA) in Rembang Regency. The method used in this research is census research conducted in the Rembnag Regency. This research was conducted on 4 chicken slaughterhouse businesses located in Rembang Regency selected by the saturated sampling method (census). The locations chosen were several villages in Rembang Regency, including Pandangan Kulon Village, Sluke Village, Kedungsapen Village, and Demang Waru Village with the consideration that the area was a place of business for Chicken Slaughterhouses (RPA) in Rembang Regency. Analysis of the data used is descriptive analysis to describe the state of the object of research, quantitative analysis to calculate the income of the chicken slaughterhouse business, and one sample t-test to compare the income of the RPA with the UMK in Rembang Regency. The results of the analysis of income calculations show that the chicken slaughterhouse business (RPA) in Rembang Regency earns a net income of Rp. 745.234.793 (seven hundred fortyfive million, two hundred and thirty-four thousand, seven hundred and ninety-three rupiah)/month. The results of the analysis of the one sample t-test of the chicken slaughterhouse business (RPA), which resulted in a significance value (0.002) smaller than the significance level (0.05), then the income obtained by the RPA business was higher than the UMK in Rembang Regency.